2010
DOI: 10.1074/jbc.m110.131441
|View full text |Cite
|
Sign up to set email alerts
|

GANP-mediated Recruitment of Activation-induced Cytidine Deaminase to Cell Nuclei and to Immunoglobulin Variable Region DNA

Abstract: AID (activation-induced cytidine deaminase) catalyzes transcription-dependent deamination of C 3 U in immunoglobulin variable (IgV) regions to initiate somatic hypermutation (SHM) in germinal center B-cells. SHM is essential in generating high affinity antibodies. Here we show that when coexpressed with GANP (germinal center-associated nuclear protein) in COS-7 cells, AID is transported from the cytoplasm and concentrated in the nucleus. GANP forms a complex with AID in cotransfected cells in vivo and in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 31 publications
0
62
0
Order By: Relevance
“…GANP interacts with AID in the cytoplasm and is involved in recruiting AID to the nucleus and to the IgV H -region DNA in B cells (29). GANP is involved in mRNA export in mammalian cells (30) and particularly in the selective export of Shugoshin-1 mRNA required for cell cycle progression through the M phase (20).…”
Section: Discussionmentioning
confidence: 99%
“…GANP interacts with AID in the cytoplasm and is involved in recruiting AID to the nucleus and to the IgV H -region DNA in B cells (29). GANP is involved in mRNA export in mammalian cells (30) and particularly in the selective export of Shugoshin-1 mRNA required for cell cycle progression through the M phase (20).…”
Section: Discussionmentioning
confidence: 99%
“…S6). With respect to AID recruitment to the IgV gene, in vivo evidence has been limited except for experiments using Ramos human lymphoma cells (44). By careful optimization of ChIP conditions, a weak AID signal was detected on the IgV gene, and this was not further enhanced by SRSF1-3 expression (Fig.…”
Section: Srsf1-3 Collaborates With Aid To Inhibit Splicing Of Ig Tranmentioning
confidence: 99%
“…For GFP or GANP overexpression (GANP O/E ) transfectants, a GFP or GFP-GANP gene was introduced into pCXN2 (chicken b-actin promoter) vector containing a neomycin-resistant cassette (33). The AID expression vector (pFB-AID-IRES-GFP) was a gift from Dr. Tasuku Honjo (Kyoto University, Kyoto, Japan).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Recently, we demonstrated that GANP interacts with cytoplasmic AID and assists its nuclear localization to augment its transport to the transcribed IgV region segment in B cells (33). In this process, the histone acetyltransferase region of GANP is involved in the selective recruitment of GANP toward the terminal region of the rearranged IgV region exons and the site-selective acetylation of the linker histone H1 (34).…”
mentioning
confidence: 99%